Akibat Hukum Pencantuman Klausula Eksonerasi dalam Polis Asuransi Jiwa serta Pengawasan oleh Otoritas Jasa Keuangan (OJK) - Esi Rahmadani (CV Rewang Rencang, 2025)
Due to the legal inclusion of exoneration clauses in life insurance policies, which are often made as standard agreements. The exoneration clause limits or removes the liability of the insurer and potentially harms the policyholder. This practice is prohibited by the Consumer Protection Act (law No. 8/1999) and OJK regulation (POJK No. 22/2023). This study also examines the effectiveness of Financial Services Authority (OJK) supervision in protecting consumers from such practices. Although prohibited, this clause is still found, indicating the gap between regulation and implementation and the need for more effective OJK supervision.